Transformasi Digital Pembelajaran IPS SD melalui Pemanfaatan E-Modul Berbasis Flipbook - Raziska Ibrahimi (Journal of Humanities, Social Sciences, and Education, 2026)
Digital transformation in education is a crucial effort to improve the quality of learning in elementary schools, including in Social Studies (IPS). This study aims to examine the digital transformation of elementary school social studies learning through the use of flipbook-based e-modules, based on various previous research findings. The study employed a literature review method with a qualitative descriptive approach. Data were obtained from 28 national and international journal articles published between 2020 and 2025 through Google Scholar, Garuda, and accredited education journals. The research process included article identification, selection based on topic suitability, content analysis, and synthesis of research findings. The study results indicate that flipbook-based e-modules make various positive contributions to social studies learning in elementary schools. The use of digital flipbooks can improve student learning outcomes, learning motivation, participation, and engagement in the learning process. For example, flipbook-based e-modules can be implemented through interactive social studies materials containing videos, images, quizzes, and contextual case studies that students can access via smartphones or laptops during classroom and independent learning activities. Furthermore, flipbooks support interactive and independent learning because the material can be accessed flexibly through digital devices anytime and anywhere. The use of flipbook-based e-modules also contributes to improving students' digital literacy and critical thinking skills through interactive and contextual learning activities. However, the implementation of flipbooks still faces several obstacles, such as limited technological infrastructure, internet access, and teachers' digital competencies. Therefore, infrastructure support, technological training, and strengthening of digital literacy are needed to ensure optimal and sustainable digital transformation of social studies learning through flipbook-based e-modules in elementary schools.